Analisis Tiang Rumah Adat dikampung Karekamangeda, Sumba Barat Daya: Tiang rumah adat - Ngongo, Paskalia; Bili, Yulita; Lede, Yulius Keremata (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the structure and meaning of the main poles in traditional houses of the community in Kampung Karekamangeda, Sumba Barat Daya Regency, East Nusa Tenggara Province. The analysis focuses on the selection of pole materials, types and positions of the main poles and supporting posts, as well as their symbolic and functional significance in the context of Sumbanese traditional architecture. Based on literature review and field observations, Sumbanese traditional houses are generally supported by four primary poles symbolizing the family entities (father-mother-son-daughter) along with several other supporting posts that sustain the wall and roof. The use of selected hard wood and the stilt house structure are also characteristic features. The analysis indicates that the main poles not only bear the structural load of the towering roof (the “tower” form) but also serve as cosmological and social status symbols among the Sumba community. Further, the study found that the selection of material, layout and maintenance of the main poles are influenced by living customary beliefs, such as the kinship system and the Marapu belief system.